Site Determination for OTEC Turbine Installation of 100 MW Capacity in North Bali Waters - Delyuzar Ilahude; Ai Yuningsih; Yani Permanawati; Mira Yosi; Rina Zuraida; N. Annisa (Marine Geological Institute of Indonesia, 2020)
This research was conducted to investigate a suitable location for the OTEC (Ocean Thermal Energy Conversion) pilot plant in North Bali. The investigation was done by calculating the theoretical potential of electric power output using the method of Uehara and Ikegami (1990) for closed cycle OTEC. OTEC power plants require a temperature difference between surface and bottom water layers at least 20°C. Temperature data were obtained from the HYCOM temperature model for a period of 9 years (2008 - 2017) at 4 points which were verified with field data taken in 2017 using KR Geomarin III. The results of field measurements show that the sea surface temperature (SST) in the study area ranges from 28 to 31°C while at depth of 800 m 5.75°C. ∆T values range from 22 to 25°C. Verification of modelling temperature and measurement temperature shows that the modeling results resemble the temperature of North Bali Waters. Analyses results for the four points showed that B-11, located in the Tedjakula area, has the largest electrical power output (71,109 MW). Thus, point B-11 is the best location for development of OTEC pilot plant in North Bali Waters.Keywords: sea water temperature, net power, OTEC closed cycle, North BaliPenelitian ini dilakukan untuk menentukan lokasi yang layak untuk pilot plant OTEC (Ocean Thermal Energy Conversion) di perairan Bali Utara. Penentuan dilakukan dengan menghitungpotensi teoritis output daya listrik menggunakan metoda Uehara dan Ikegami (1990) untuk OTEC siklus tertutup. Pembangkit listrik OTEC membutuhkan perbedaan suhu antara lapisan permukaan dan lapisan dalam sebesar 20°C atau lebih. Data suhu didapatkan dari model suhu HYCOM untuk jangka waktu 9 tahun (2008 – 2017) pada 4 titik yang diverifikasi dengan data lapangan yang diambil pada tahun 2017 dengan menggunakan KR Geomarin III. Hasil pengukuran lapangan menunjukaan bahwa suhu permukaan laut (SPL) daerah penelitian berkisar 28-31°C dan suhu air pada kedalaman 800 m adalah 5,75°C. Nilai ∆T berkisar 22-25°C. Verifikasi suhu hasil pemodelan dengan suhu hasil pengukuran menunjukkan bahwa suhu hasil pemodelan dapat mewakili suhu perairan Bali Utara. Hasil analisis yang dilakukan pada 4 titik menunjukkan bahwa titik B-11 yang terletak di daerah Tedjakula memberikan output daya listrik terbesar (71,109 MW). Titik B-11 merupakan lokasi terbaik untuk pengembangan pilot plant OTEC di perairan Bali Utara.Kata kunci: suhu air laut, daya listrik, OTEC siklus tertutup, Bali Utara